2009
DOI: 10.1007/s00330-009-1689-7
|View full text |Cite
|
Sign up to set email alerts
|

Does joint alignment affect the T2 values of cartilage in patients with knee osteoarthritis?

Abstract: Objective To assess the relationship between T2 values of femorotibial cartilage and knee alignment in patients with clinical symptoms of medial osteoarthritis (OA). Methods Twenty-four patients (mean age ± standard deviation, 62.5±9.9 years) with clinical symptoms of medial knee OA, 12 with varus and 12 with valgus alignment of the femorotibial joint, were investigated on 3T MR using a 2D multi-echo spin echo (MESE) sequence for T2 mapping. Analysis of covariance, Spearman correlation coefficients, exact Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…The patellar cartilage was shown to demonstrate more in vivo deformation than the femoral and tibial cartilages with weight-bearing loaded activities ( 30 ). Our results are also in keeping with those of Friedrich et al ( 32 ), who demonstrated that cartilage T2 values in the medial compartment Multiple previous studies of the prevalence of OA (23)(24)(25) evaluated the presence and severity of OA primarily with use of the radiographybased Kellgren and Lawrence grading system ( 26 ), which is heavily dependent on osteophytes for classifi cation of disease and suffers from its own morphologic abnormalities, particularly cartilage lesions, at 3-T MR imaging. We found a signifi cant longitudinal increase in tibiofemoral cartilage T2 values in asymptomatic individuals and demonstrated that increased progression of cartilage abnormalities correlated with a greater increase in T2.…”
Section: Discussionsupporting
confidence: 92%
“…The patellar cartilage was shown to demonstrate more in vivo deformation than the femoral and tibial cartilages with weight-bearing loaded activities ( 30 ). Our results are also in keeping with those of Friedrich et al ( 32 ), who demonstrated that cartilage T2 values in the medial compartment Multiple previous studies of the prevalence of OA (23)(24)(25) evaluated the presence and severity of OA primarily with use of the radiographybased Kellgren and Lawrence grading system ( 26 ), which is heavily dependent on osteophytes for classifi cation of disease and suffers from its own morphologic abnormalities, particularly cartilage lesions, at 3-T MR imaging. We found a signifi cant longitudinal increase in tibiofemoral cartilage T2 values in asymptomatic individuals and demonstrated that increased progression of cartilage abnormalities correlated with a greater increase in T2.…”
Section: Discussionsupporting
confidence: 92%
“…loss of superficial cartilage with long relaxation times). Instead, this change may potentially be attributed to a shift towards more varus induced by narrowing of the medial joint space 38 .…”
Section: Discussionmentioning
confidence: 99%
“…4 In cohorts of less than 30 individuals, people with medial knee OA who had varus alignment were found to have higher cartilage T1rho and T2 than those with valgus alignment. 20,55 Most of these studies either were in healthy cohorts or had a small sample size. Longitudinal studies in larger samples, like the OAI cohort, are needed to understand the effect of these OA risk factors on cartilage degeneration over time.…”
Section: Discussionmentioning
confidence: 99%